Frequent Bullying Involvement and Brain Morphology in Children - Muetzel, Ryan L.; Mulder, Rosa H.; Lamballais, Sander; Cortes Hidalgo, Andrea P.; Jansen, Pauline; Güroğlu, Berna; Vernooiji, Meike W.; Hillegers, Manon; White, Tonya; El Marroun, Hanan; Tiemeier, Henning (Frontiers in Psychiatry, 2019)
Background Over the past few decades, bullying has been recognized as a considerable public health concern. Involvement in bullying is associated with poor long-term social and psychiatric outcomes for both perpetrators and targets of bullying. Despite this concerning prognosis, few studies have investigated possible neurobiological correlates of bullying involvement that may explain the long-term impact of bullying. Cortical thickness is ideally suited for examining deviations in typical brain development, as it has been shown to detect subtle differences in children with psychopathology. We tested associations between bullying involvement and cortical thickness using a large, population-based cohort. Methods The study sample consisted of 2,602 participants from the Generation R Study. When children were 8 years old, parents and teachers reported on common forms of child bullying involvement (physical, verbal, and relational). Questions ascertained whether a child was involved as a perpetrator (n=82), a target of bullying (n=92), as a combined perpetrator and target of bullying (n=47) or uninvolved in frequent bullying (n=2,381). High-resolution structural magnetic resonance imaging was conducted when children were 10 years of age. Cortical thickness estimates across the cortical mantle were compared amongst groups. Results Children classified as frequent targets of bullying showed thicker cortex in the fusiform gyrus compared to those uninvolved in bullying (B = 0.108, pcorrected < 0.001). Results remained consistent when adjusted for socioeconomic factors, general intelligence, and psychiatric symptoms. Children classified as frequent perpetrators showed thinner cortex in the cuneus region, however this association did not survive stringent correction for multiple testing. Lastly, no differences in cortical thickness were observed in perpetrator-targets. Discussion Bullying involvement in young children was associated with differential cortical morphology. Specifically, the fusiform gyrus, often involved in facial processing, showed thicker cortex in targets of frequent bullying. Longitudinal data are necessary to demonstrate the temporality of the underlying neurobiology associated with bullying involvement.